Pengaruh NPM, CR, EPS, PER, DPS Terhadap Harga Saham Pada Perusahaan Manufaktur Di Bursa Efek Indonesia Pasca Pandemi Covid-19 - Annisa Nauli Sinaga; Kristina Wijaya; Amanda Parawansa; Mitha Christina Ginting (Journal of Economic, Bussines and Accounting (COSTING), 2024)
Companies listed on the IDX are competing to attract investors to buy their shares. The purpose of this study is to examine the effect of NPM, CR, EPS, PER and DPS with a simulated and significant effect on Share Prices in Manufacturing companies listed on the Indonesia Stock Exchange for the 2019-2022 period. This study used quantitative research and sampling techniques using purposive sampling. The population in this study is 76 Consumer Goods Manufacturing Subsector. The sample of this study amounted to 14. The model is with multiple linear regression. The result is that NPM has no partial and significant effect on the Share Price of Manufacturing companies listed on the Indonesia Stock Exchange for the 2019-2022 period. CR does not have a partial and significant effect on the Share Price of Manufacturing companies listed on the Indonesia Stock Exchange for the 2019-2022 period. EPS has a partial and significant effect on the Share Price of Manufacturing companies listed on the Indonesia Stock Exchange for the 2019-2022 period. PER has a partial and significant effect on the Share Price of Manufacturing companies listed on the Indonesia Stock Exchange for the 2019-2022 period. DPS does not have a partial and significant effect on the Share Price of Manufacturing companies listed on the Indonesia Stock Exchange for the 2019-2022 period. NPM, CR, EPS, PER and DPS have a simulated and significant effect on the Share Price of Manufacturing companies listed on the Indonesia Stock Exchange for the 2019-2022 period. Keywords: NPM, CR, EPS, PER, DPS and Stock Price